Working Capital Management Policy and The Financial Performance of Food and Beverages Companies in Nigeria - Yahaya Yusuf; Mohammed Sani (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2018)
This study is set to examine the relationship between working capital management policy and profitability of quoted food and beverages companies in Nigeria. The population comprises a sample of ten (10) food and beverage companies quoted on the Nigerian Stock Exchange. The study used secondary data for a period of ten (10) years (2005-2014) and was analyzed using descriptive and inferential statistics with the aid of Stata version 13. Two research hypotheses were formulated and tested. It was found that, there is no significant relationship between receivable collection period (RCP) policy and profitability of quoted food and beverage companies in Nigeria. However, it was recommended that the management should identify the level of inventory which allows for uninterrupted production but reduces the investment in raw materials and minimizes reordering cost and hence increases profitability. The management should reduce their RCP from 53 days on the average to at most 30 days by instituting adequate control and flexible credit policy.